Media Conglomeration and Worker Commodification: Analyzing the Political Economy of Media Spatialization in Indonesia - Sunandar, Asep; Briandana, Rizki (Social and Economic Bulletin, 2024)
The rapid transformation of the media industry, marked by conglomeration and spatialization, raises concerns about the commodification of media workers. This study investigates the practice of media spatialization within PT: Media Nusantara Citra (MNC) and its impact on the commodification of reporters and camera persons. Drawing on Vincent Mosco’s theory of political economy and Foucault’s power relations framework, the study employs a critical case study method. Data were collected through in-depth interviews with key informants and observations, complemented by secondary data. The findings reveal three typologies of spatialization—open, closed, and hidden—and their implications for media workers, including labor, psychological, economic, and capability exploitation. While efficient for the corporation, the integration system has led to excessive workloads, disproportionate wages, and diminished autonomy for media workers. Theoretically, this study enriches the discourse on media political economy by affirming the relevance of spatialization in understanding contemporary media practices and worker commodification. Practically, the findings advocate for strengthening trade unions and regulatory enforcement to safeguard media workers’ rights and promote a more equitable media ecosystem. The study underscores the need for corporate strategies prioritizing employee well-being to mitigate the adverse effects of conglomeration-driven spatialization.